Language Ideologies and Decoloniality in Vernac News - Mkula, Lwazi (School of Education, 2019)
This study examines the language ideologies constructed in the publication Vernac News produced by students at the University of Cape Town. These language ideologies seek to challenge and subvert dominant language practices within the university community. These dominant language ideologies are challenged through various ways, such as the specific use of indigenous African languages, and the use of urban vernaculars in formal contexts, English platforms such as the student newspaper. The study also looks at the ways in which media are used as tools for social activism as seen in the Vernac News publication. The study treats language as a social tool, integral in constructing identities, meaning-making, and accounting for the lived experience of its users. The study used twelve articles from six issues of Vernac News and interviews as the source of data. Language ideologies looks at the way in which languages and speakers are perceived and treated in society. In the period of the call to decolonise the university and the curriculum in South Africa, it was particularly important for the study to explore what this meant for language and the language practices within the university. The research explores various understandings, and discourses, of Decolonisation and Decoloniality, and other related discourses, as discussed by scholars such as Maldonado-Torres, Mignolo, Santos, amongst others. Additionally, the study examines the practices of ‘languaging’ in several urban contexts, let these be spoken or written accounts. The study is largely qualitative and makes use of linguistic ethnography to generate data from the various available sources. The linguistic ethnography approach here is coupled with Critical Discourse Analysis as tools for data analysis. The data analysis process foregrounds and highlights situated language uses in seven selected texts from the publication as well as interviews with members involved in the early development of the publication. The analysis looks at the various ways in which practices such as Translanguaging are essential language practices in the creation of identity, history and resistance and challenging of the hegemony of English in the university community. The study found that the language practices of students involved in the publication were capable of challenging and subverting dominant language practices in formal context such as the university space, thus, it enabled the development of a truly integrated language ideology. The study also confirmed that language is social, and can reflect the social condition within which it operates, through the development of Discourses on social issues such Decolonisation and Decoloniality.